The environmental consequences of foreign finance inflows and economic performance in Africa - Nkemdilim Iheanachor; Chris Ike Ogbechie; Azuka Elvis Ozegbe (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
The purpose of this study was to examine the impact of foreign finance inflows and economic performance on environmental degradation in Africa. The study was motivated by the quest to reexamine the validity of the environmental Kuznets curve (EKC) theory in 15 selected African economies by practically decomposing the total environmental effects of foreign finance into three strands, namely scale, technique, and composition effects. The panel dataset contained the 15 largest economies selected from the five regions of the African continent from 1990 to 2020 and ensured the used of 31 observations for each country. To simultaneously guarantee heterogeneity among the long-run and short-run coefficients, the study employed pooled mean group (PMG) estimator of the dynamic heterogeneous panel auto-regressive distributed lag (panel ARDL) model as its analytical technique. The study revealed that economic performance was negatively and positively related to environmental degradation in the short-run and long-run, respectively. This confirms the existence of an inverted U-shaped relationship between economic performance and environmental degradation and also validates the existence of the environmental Kuznets curve (EKC) hypothesis. Moreover, foreign finance was inversely related to environmental degradation, which implies that poor environmental quality cannot be directly linked to foreign capital inflows among the investigated countries.
Keywords: C10; F43; H10; 330; Foreign finance; environmental degradation; economic performance; environmental Kuznets curve (EKC)